1991
DOI: 10.1152/jappl.1991.71.2.727
|View full text |Cite
|
Sign up to set email alerts
|

Lung edema formation following inhalation injury: role of the bronchial blood flow

Abstract: We investigated the contribution of the bronchial blood flow to the lung lymph flow (QL) and lung edema formation after inhalation injury in sheep (n = 18). The animals were equally divided into three groups and chronically prepared by implantation of cardiopulmonary catheters and a flow probe on the common bronchial artery. Groups 1 and 2 sheep were insufflated with 48 breaths of cotton smoke while group 3 received only room air. Just before injury, the bronchial artery of group 2 animals was occluded. The oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Magno and Fishman (10) showed that the tracheal bronchial artery is one of the major sources of blood to the lung. We have also reported that occlusion of the bronchial artery prevented the increase in pulmonary transvascular fluid flux seen with inhalation injury (3,12). These findings were recently confirmed by others (7).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Magno and Fishman (10) showed that the tracheal bronchial artery is one of the major sources of blood to the lung. We have also reported that occlusion of the bronchial artery prevented the increase in pulmonary transvascular fluid flux seen with inhalation injury (3,12). These findings were recently confirmed by others (7).…”
Section: Discussionsupporting
confidence: 84%
“…Hemodynamic variables and blood gases were obtained at 3,6,12,18,24,30,36,42, and 48 h after injury in all groups.…”
Section: Methodsmentioning
confidence: 99%
“…This statement is supported by the results of three independent methods: the decrease in lung tissue myeloperoxidase activity, an index of neutrophil accumulation (21); the lower histological scores for alveolar as well as interstitial neutrophils; and the reduced number of neutrophils in the lung lymph. Neutrophil adherence to the endothelium can directly induce endothelial injury resulting in vascular leakage and eventually pulmonary edema (22, 23). The clinical relevance of neutrophils in the pathogenesis of inhalation injury was confirmed by Basadre et al (24), who demonstrated that in leukocyte-depleted sheep the characteristic changes, such as a fall in PaO2/FIO2 ratio and an increase in MPAP and transvascular fluid flux, were markedly attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have shown that the flow of lymph from a sheep leg fistula goes up after smoke inhalation combined with burn (Lalonde et al, 1992). We and others have also shown that the bronchial arteries play a major role in smoke-induced pulmonary edema perhaps by carrying mediators of inflammation from the severely injured proximal airway to the lung parenchyma (Hales et al, 1989;Adbi et al, 1991;Efimova et al, 2000).…”
Section: Introductionmentioning
confidence: 75%